PENGARUH KOMPENSASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. SPESIAL DELEVERI KARGO SURABAYA - Putra Febria Rakhmadian; Mei Retno Adiwati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
In achieving the company's goals, maximum attention is needed in improving the performance of each employee so that later they can obtain maximum results as expected, by making efforts to pay attention to and manage performance in a predetermined framework, which includes objectives, standards and competency requirements. planned. Performance is an achievement or result achieved by an individual in relation to the duties and authorities assigned to him. This study aims to examine the effect of compensation and work stress on the performance of employees of PT. Cargo Deleveri Special. The population used in this study are employees at PT. Special Cargo Deleveri Surabaya in the operational section as many as 52 people and the sample of this study used a saturated sample. In this study using quantitative methods using structural equation modeling and partial least squares (PLS) as analytical tools. This study found that compensation is able to contribute to improving employee performance and work stress has a negative contribution to improving employee performance